Pengaruh Kinerja Keuangan terhadap Nilai Perusahaan dengan Good Corporate Governance sebagai Variabel Moderasi pada Perusahaan Food and Beverage yang Terdaftar di Bursa Efek Indonesia - Sri Hardianti; Eka; Rina; Arianti Latif; Asriany (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to examine and analyze the effect of financial performance on firm value. This study also examines the effect of moderating Good Corporate Governance on the relationship between Financia Performance (Return on Assets) and Corporate Value. This type of research is quantitative research. The popilation in this study are Food and Beverage companie listed on the Indonesia Stock Exchange in the 2016-2020 periode with a total of 30 companies observed. The sampling technique used is purpose sampling based on certain criteria. Based on these criteria, obtained a sample of 8 compains. Testing research data using simple linear regression analysis to test the first hypothesis and multiple linear regression analysis using moderated regression analysis (MRA) to test the second hypothesis. The results of the research on the first hypothesis using simple linear regression analysis show that the financial performance projected by Retur on Assets (ROA) has a significant effect on the moderating variable, Good Corporate Governance (Institusional Ownership) is not able to moderate the relationship between Financial Performance Return om Assets anf Firm Value.